Evaluation of Medications Used for Hospitalized Patients With Sleep Disturbances: A Frequency Analysis and Literature Review. (February 2023) - White, Brittany; Snyder, Heather S.; Patel, Megan Van Berkel
Purpose: Poor sleep during hospitalization is common and implicated in worse patient outcomes. Despite implementation of non-pharmacologic techniques, medications are still frequently required. The study objective is to assess the frequency of new medications administered for sleep in hospitalized patients and to review literature evaluating these drug therapies in the inpatient setting. Methods: This retrospective study included adult inpatients if they received a new medication for sleep during a 5-day period. Patients were excluded if the medication was continued from home or if sleep was not the documented indication. For the literature review, a MEDLINE search was conducted to identify studies pertaining to pharmacotherapy for sleep in hospitalized patients. Results: Of 1, 968 patient-days reviewed, a medication for sleep was given for 166 patient-days (8.4%) in 78 patients. Melatonin was most commonly received (70.5%), followed by benzodiazepines (9.6%). A review of antihistamines, benzodiazepines, melatonin, quetiapine, trazodone, and Z-drugs (non-benzodiazepine hypnotics) was conducted and 23 studies were included. Conclusions: Despite widespread use of pharmacotherapy for sleep, there is a paucity of data evaluating use in the inpatient setting. Although there is significant heterogeneity among studies, melatonin has the strongest evidence for use and is an attractive option given its lack of adverse reactions and drug interactions. Benzodiazepines and Z-drugs were also frequently utilized; however, their reduced clearance in the elderly and potential for compounded sedative effects should be weighed heavily against potential sleep benefits. Antipsychotic agents cannot be recommended for routine use due to limited data and the potential for significant adverse effects.